A Young Woman with Inevitable Limb Loss - Tresukosol, Damras; Ruansetakit, Chanean; Kongsayreepong, Suneerat (Siriraj Medical Journal, 2020)
We report a pitfall in the management of a young 43-year-old female who presented with a history of claudication and threaten limb loss. Inappropriate axillobifemoral bypass graft surgery was performed, resulting in perioperative graft failure with progressive inevitable gangrene of the left leg. Rescue surgery was performed to salvage the right limb but she developed perioperative myocardial infarction. Delayed amputation was justified, pre-operative cardiac evaluation and aggressive percutaneous coronary intervention was performed followed by an uneventful definitive below-knee amputation of left leg. The patient was discharged and was referred for a left leg prosthesis.